Evaluation of Glycated Albumin and Microalbuminuria as Early Risk Markers of Nephropathy in Type 2 Diabetes Mellitus - Suresh Babu Kondaveeti; Kumaraswamy D; Shishir Mishra; Aravind Kumar R; I Anand Shaker (Journal of Clinical and Diagnostic Research, 2013)
Introduction: Since Glycated Albumin (GA) reflects short term variations and glycated protein shows degrees of hyperglycaemia, the objective of this study was to find GA and microalbuminuria as a early risk markers along with the duration of Uncontrolled Diabetes Mellitus in type 2 diabetic nephropathy. Material and Methods: The present cross-sectional study included randomly selected Uncontrolled Type 2DM (n = 75), controlled Type 2DM (n = 75) and healthy controls (n = 75). Their fasting venous blood samples were obtained for GA and serum creatinine, while their morning urine samples were obtained for detection of microalbuminuria. Statistical analysis was done by using SPSS, version 16.0. One-Way ANOVA was performed. All p-values which were ≤ 0.05 were considered as statistically significant. Results: The mean GA, microalbuminuria and serum creatinine were the highest in Uncontrolled DM as compared to those in Controlled DM respectively. Microalbuminuria and GA had a significant correlation with the duration of diabetes (p<0.0001). Conclusion: The present study identified that the risk of microalbuminuria increased with a poor glycaemic control. A persistent increase in GA and microalbuminuria may be considered as risk markers in diabetic nephropathy. Therefore, a regular screening for microalbuminuria and estimation of GA can help in the clinical management, to prevent complications.